Intergenerational mobility of education in Vietnam: Evidence from the Vietnam War - Khoa Vu; Maria C. Lo Bue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Vietnam's education system has recently attracted international attention for exceptional learning outcomes and success in improving schooling outcomes over a short period, despite being a lower-middle-income country. One potential explanation is the substantial increase in parental schooling after the Vietnam War ended in 1975, which might have led to better educational outcomes for the next generation. This study examines the causal effect of parental schooling on children's educational attainment in Vietnam. We exploit variation in parental exposure to aerial bombing at an early age to identify the effect of parental schooling. Our instrumental variable estimates indicate that the father's schooling does not affect a child's educational outcomes. Furthermore, we find that although parental bombing exposure reduced their schooling, it did not affect children's educational outcomes or parental investment in their children. Taken together, these findings suggest that Vietnam's recent success in education is not caused by the rise in the schooling of the parents of today's children after the war ended in 1975.
Keywords: I20; J62; C36; 330; intergenerational mobility of education; Vietnam; Vietnam War